Chronic pain and depression - Davide Cristina (Publiediting, 2021)
Chronic pain is a major public health problem worldwide, recent studies have found that the role of neuronal plasticity is at the root in the development of chronic pain and depression. Both pathological condition share neurophysiological mechanism and neurotransmitters, which has implications for treating both simultaneously.